Numerical approach for simulation of Palmer cooling - Dolinska, M.E.; Doroshko, N.L. (Вопросы атомной науки и техники, 2018)
In this paper the time domain algorithm is described and applied for the Palmer Cooling method. The possibility of using the Palmer system in such case for simultaneous longitudinal and transverse cooling by a suitable choice of the pickup to kicker distance was described by Hereward [1, 2]. Using his method the special computer code has been developed to calculate beam cooling in time domain approach.